Accelerating cancer genomics research in Sub-Saharan Africa - Ivanga, Mahinè; Iroungou, Berthe Amelie; Bigoundou-Nzamba, Stephane; Bisseye, Cyrille (Frontiers in Oncology, 2025)
Cancer is an increasing public health concern for Sub-Saharan African (SSA) countries, a region that is, unfortunately, already marked by the persistent presence of infectious diseases. Noticeably, in SSA, the universal approach to cancer treatment still prevails, whereas elsewhere, cancer treatment has shifted towards precision medicine. Definitely, the region faces many challenges that impede cancer genomics research despite its tremendous potential solution. Indeed, Genomics research could provide critical insights into the genetic determinants of cancers prevalent in SSA, enabling more precise and effective diagnosis, treatment, and prevention strategies tailored to local specificities. Therefore, shifting to precision medicine in this region is critical to tackle increase in cancer cases among SSA populations.